Enhanced Sensitive Electrochemical Sensor for Simultaneous Catechol and Hydroquinone Detection by Using Ultrasmall Ternary Pt‐based Nanomaterial. Issue 6 (30th March 2021) - Arsalan, Muhammad; Qiao, Xiujuan; Awais, Azka; Wang, Yahui; Yang, Shuying; Sheng, Qinglin; Yue, Tianli
Abstract: The simple and effective method for the novel synthesis of Pt‐based nanoparticle was presented with high efficiency. The sensitive catalyst for the simultaneous detection of catechol and hydroquinone was prepared by depositing ternary metal complex on fluorine‐doped tin‐oxide (FTO). The composition and morphology of nanomaterials were characterized by TEM, HRTEM, XRD, XPS, and EDS (energy dispersive spectroscopy). The size of the Pt‐based nanomaterial was about 5±1 nm. The electrochemical performance of the modified catalyst was studied by CV, DPV, and EIS. The modified PtNiCu@FTO catalyst possessed good electro‐oxidation activity for hydroquinone and catechol and used for simultaneous detection of catechol and hydroquinone at scan rate of 20 mV s −1 (vs. Ag/AgCl). Detection responses were found in the ranges of 5–2900 μM for hydroquinone and 5–3000 μM for catechol. The detection limits (LOD) for HQ and CC were observed as 0.35 and 0.29 μM, respectively. The sensitivity of HQ and CC were 1515.55 and 1485 μA mM −1  cm −2, respectively. The prepared nanomaterial were effectively applied for the determination of CC and HQ in real samples. Abstract :